Chitosan nerve tube for primary repair of traumatic sensory nerve lesions of the hand without a gap: study protocol for a randomized controlled trial - Neubrech, Florian G.; Heider, Sina; Harhaus-Wähner, Leila; Bickert, Berthold; Kneser, Ulrich; Kremer, Thomas (Trials, 2016)
Complex peripheral nerve injuries of the hand include at least 300,000 cases per year in Europe. The standard treatment involves a microsurgical end-to-end suture of traumatic sensory nerve lesions of the hand without a gap. The objective of this study protocol is to evaluate whether the additional use of a chitosan nerve tube in primary repair of traumatic sensory nerve lesions of the hand without a gap has an effect on the recovery of sensitivity.
Gesehen am 26.01.2021